The Effect OF Brand Image and Customer Perceived Value On Telkomsel’s Brand Loyalty - Tarmidi, Didi; Fauziah, Nurul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to determine the influence of Brand Image and Customer Perceived Value on Brand Loyalty on Telkomsel. The sample in this study was 100 respondents. The data used are primary data analyzed using multiple linear regression equations, hypothesis tests (t-test and f test), and coefficient of determination (R2). The results of the study obtained Y = 3.381 + 0.170X1 + 0.387X2. A constant of 3,381 Brand Loyalty before being influenced by Brand Image and Customer Perceived Value towards Brand Loyalty at Telkomsel. The calculation result shows the value of R2 = 0.426. This means that 42.6% of the variation in the rise and fall of Brand Loyalty is influenced by the variables Brand Image and Customer Perceived Value. While the remaining 57.4% was influenced by other variables that were not found in this study.